THE IMPROVEMENT OF COMMUNICATE SKILL AND CONCEPT’S MASTERY ON LEARNING CYCLE 3E - Ryzal Perdana; Nina Kadaritna; Tasviri Efkar (Universitas Lampung, 2013)
Concidentally educator in chosed instruction model influence of communicate skill level and concept’s mastery. Communicate skill and concept’s mastery to training by instruction model appropriate would be accompany student for more significant instruction. The research for get a effective instruction model in increase communicate skill and concept’s mastery to acid-based materials. Learning Cycle 3E model consist from 3 phase : Exploration, Explanation, Elaboration. Sample in research is students in senior high school state 1 pekalongan, Class XI sains one and XI sains four, even semester school year 20012-2013 have a same characteristics. The research is kuasi-experiment method with non equivalent pretest and posttest control group design. Effectiveness LC 3E measure and based on significant gain increase. The research indicated average value N-gain communicate skill. For control and experiment class each 0,55 and 0,66 and average N-gain concept’s mastery for control and experiment class 0,53 and 0,65. Based on hypothesis test, know that class with LC 3E instruction have communicate skill and concept’s mastery more high than class with convensional instruction. In this matter , indicated that LC 3E effective to increase communicate skill and concept’s mastery.Kata kunci : keterampilan mengkomunikasikan, model Learning Cycle 3E, penguasaan konsep